DIGITALISASI UMKM BATIK MALANG SEBAGAI OPTIMALISASI PELESTARIAN KEARIFAN LOKAL DI MASA PANDEMI COVID-19 - Salma Hanin Zayyana; Elya Kurniawati; Kun Sila Ananda (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
The Covid-19 pandemic requires Malang Batik MSME actors to leave old patterns and create new opportunities and innovations, namely from product development to marketing transition from offline to online. Seeing this, there are opportunities and potentials to preserve local wisdom through MSME Batik Malang which is digitizing marketing. This study aims to determine the application of social media as a means of digitizing marketing and the effect of digitalization of marketing in optimizing the preservation of local wisdom during the Covid-19 pandemic. The method used is descriptive qualitative. Determination of informants from this study using purposive sampling technique. This research was conducted at Batik Blimbing, Soendari Batik Art, Poesaka Djagad, Batik Pandan Arum, Lembayung Batik, and Batik Niati. The results of the study were examined using the perspective of social change and AGIL Theory. The results of the study show that several Malang Batik MSMEs have digitized marketing before the Covid-19 pandemic and several others have just digitized marketing during the Covid-19 pandemic. MSME Batik Malang continues to innovate in order to continue to achieve sales targets and preserve local wisdom during the pandemic. This was done because the Malang Batik MSME actors were increasingly aware of the advancement of ICT and had to take advantage of it. The use of social media features such as Instagram, Facebook, WhatsApp, Tokopedia, Shopee, etc. which can provide recommendations and testimonials on products being marketed so as to arouse curiosity in potential consumers in the market. In addition, due to the development of information related to Batik Malang through social media, it is also included in the effort to preserve the values ​​contained in the local wisdom of Batik.